PREVALENSI HBsAg, Anti HBs, DAN Anti HCV PADA MAHASISWA FAKULTAS KEDOKTERAN PRE KLINIS DI BALI PERIODE JANUARI 2013 – JUNI 2014 - Murprayana, Krishna; Budayanti, Ni Nyoman Sri (E-Jurnal Medika Udayana, 2017)
Hepatitis B and C is a deadly and contagious disease. Indonesia is a developing country that has a high endemicity of hepatitis B. Hepatitis screening aimed to determine the presence or absence of hepatitis virus infection in a person’s body, which can later be used to prevent infection by vaccination. The high risk factor of hepatitis infection in Indonesia is the main reason for population to do a screening procedure or early detection of hepatitis, especially hepatitis B and C. The aim of study was to determine the prevalence of student of the Faculty of Medicine with HBsAg, Anti-HBs and Anti-HCV positive. The design of this study was a descriptive cross-sectional. Data was collected using secondary data from medical students who was screened in Biology Molecular Laboratory of Udayana Medical Faculty. There were 302 samples analyzed data, consisting of 283 inclusion data and 19 data were excluded. Based on all the data that were inclusion, the sample consisted of 112 (39.6%) males and 171 (60.4%) women. From the 283 students of the Faculty of Medicine who have been screened, there are two students (0.7%) with positive HBsAg and 8 students (2.8%) with Anti-HBs positive. From the total sample of data, there is no medical students with Anti HCV positive. From the total of data, the sample consisted of female more than male. Students with HBsAg positive consisted of one male student and one female student, while the Anti-HBs positive consisted of female more than male. Keywords: Screening, medical student, hepatitis B, hepatitis C, HBsAg, Anti HBs, Anti HCV .